ENGINEERING STUDENTS’ ENGLISH PROFICIENCY DEVELOPMENT THROUGH AR TECHNOLOGIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper explores the implementation of Augmented Reality (AR) technology as an innovative tool for enhancing English language skills among engineering students. In the context of rapid technological integration into educational processes, AR emerges as a powerful instrument for creating an effective learning environment, particularly relevant for future engineers who will work with cutting-edge technologies. While this topic has been extensively researched internationally over the past decade, the application of AR in English language teaching for technical specialists remains understudied in the domestic educational space. This study aims to unveil the potential of AR applications and platforms for developing professionally-oriented language competencies among engineering students. The research analyzes the didactic capabilities of mobile AR applications and proposes a comprehensive set of exercises designed to develop technical vocabulary and communication skills in a professional context. Special attention is paid to creating immersive scenarios that simulate real industrial situations, where engineering students can practice professional English while interacting with virtual objects and delivering technical presentations. This study contributes to the growing body of literature on technology-enhanced language learning by demonstrating how AR can be effectively integrated into ESP (English for Specific Purposes) curriculum for engineering students. The findings suggest that AR-enhanced learning environments significantly improve students’ engagement, technical vocabulary retention, and confidence in professional communication scenarios.